Sustainable Marketing Model: Market Research, Marketing Capability and Entrepreneurial Orientation in Indonesia - Muhajir, Ali (International Journal of Business, Law, and Education, 2024)
This study explores the application of the Sustainable Marketing Model in Indonesia's ever-changing corporate environment. The study involved 275 organizations from a variety of industries, and the sample size was large. This allowed for important insights into how market research, marketing expertise, and entrepreneurial spirit shape sustainable marketing strategies. The associations between the important variables were investigated using measurement model analysis, structural model analysis, and descriptive statistics. Positive developments in sustainable marketing practices are shown by the results, which also show strong and substantial relationships between market research, marketing competence, entrepreneurial orientation, and sustainable marketing. Measures of goodness-of-fit provide evidence for the model's general suitability. Specific tactics to improve market research, marketing skills, and entrepreneurial attitudes are among the implications for firms. The study establishes the foundation for other research projects and adds to the developing field of sustainable marketing in Indonesia